Rice caryopsis development II： Dynamic changes in the endosperm - Wu, Xiaoba; Liu, Jinxin; Li, Dongqi; Liu, Chun-Ming (Journal of integrative plant biology, 2016)
The rice endosperm plays crucial roles in nourishing the embryo during embryogenesis and seed germination. Although previous studies have provided the general information about rice endosperm, a systematic investigation throughout the entire endosperm developmental process is still lacking. In this study, we examined in detail rice endosperm development on a daily basis throughout the 3o-day period of post-fertilization development. We observed that coenocytic nuclear division occurred in the first 2 days after pollination （DAP）, cellularization occurred between 3 and 5 DAP, differentiation of the aleurone and starchy endosperm occurred between 6 and 9 DAP, and accumulation of storage products occurred concurrently with the aleurone/starchy endosperm differentiation from 6 DAP onwards and was accomplished by 21 DAP. Changes in cytoplasmic membrane permeability, possibly caused by programmed cell death, were observed in the central region of the starchy endosperm at 8 DAP, and expanded to the whole starchy endosperm at 21 DAP when the aleurone is the only living component in the endosperm. Further, we observed that a distinct multi-layered dorsal aleurone formed near the dorsal vascular bundle, while the single- or occasionally two-cell layered aleurone was located in the lateral and ventral positions of endosperm. Our results provide in detail the dynamic changes in mitotic divisions, cellularization, cell differentiation, storage product accumulation, and programmed cell death that occur during rice endosperm development.